Novel ASR isolated from drought stress responsive SSH library in pearl millet confers multiple abiotic stress tolerance in PgASR3 transgenic Arabidopsis - Meena, Rajendra Prasad (Plant physiology and biochemistry : PPB, 2020)
Copyright © 2020 Elsevier Masson SAS. All rights reserved.